Pengaruh Variasi Menu, Harga, dan Suasana Tempat terhadap Kepuasan Konsumen pada Usaha Ayam Penyet Simbok Djogja - Merli Mai Damayanti; Hanny Mellyana Putri; Muhammad Ghifari Fauzan Faridz; Siti Aliya; Siti Salma Nushrotillah; Muhammad Gusfi Ardiansyah (LPPM Politeknik Pratama, 2025)
This study analyzes the effect of menu variety, pricing, and dining atmosphere on customer satisfaction at Ayam Penyet Simbok Djogja. A quantitative approach was applied using questionnaires distributed to 50 respondents in Ciawi. The results show that menu variety and fair pricing significantly influence customer satisfaction, while dining atmosphere has no direct effect. Consumers are more satisfied when offered diverse menus that match their preferences and prices considered reasonable. Although atmosphere is not a main factor, cleanliness and comfort still support a positive dining experience. These findings provide useful insights for culinary businesses in designing menus, setting prices, and maintaining a pleasant environment to improve customer satisfaction.